Autologous blood clots: a natural biomaterial for wound healing - Richter, David M.; Ku, Jennifer C.; Keckler, Kayla E.; Burke, Lacey R.; Abd, Genevieve M.; Li, Yong (Frontiers in Materials, 2023)
Repair after injury in mammalian tissue involves a complex cascade of events, with the formation of local blood clots being essential for the initial phases of wound healing. As a result, emerging research has sought to harness this biological activity to generate a pro-regenerative biomaterial to speed up wound healing. According to recent studies, "blood clots" created in vitro can be employed as an orthobiologic-based biomaterial for promoting tissue regeneration. Even though such research is still in its early phases, numerous studies show encouraging results that suggest autologous blood clots created in vitro might be a valuable treatment for soft tissue and orthopedic injuries. In this article, we discuss the function of blood clots in physiologic healing, how exogenous material can affect this process, and the most recent clinical research that proposes the use of autologous blood clots as a therapeutically beneficial biomaterial.